Republic of Belarus : 2011 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2011)
Belarus's economy grew rapidly but remained vulnerable to external shocks. Under the IMF-supported program, Belarus avoided loss of output during the global recession, contained inflation, and increased gross reserves. The structural reform agenda focused on economic liberalization, a shift in investment from the housing sector to the tradable sector, a smaller role of the state, and the development of the financial sector. Post-program monitoring was proposed. Establishing a development bank to administer lending under government programs would free the central bank and commercial banks from quasi-fiscal activity.